Palliative resection of the primary tumor in 442 metastasized neuroendocrine tumors of the pancreas: a population-based, propensity score-matched survival analysis - Hüttner, Felix; Schneider, Lutz; Tarantino, Ignazio; Warschkow, René; Schmied, Bruno; Hackert, Thilo; Diener, Markus K.; Büchler, Markus W.; Ulrich, Alexis (Langenbeck's archives of surgery, 2015)
There is an ongoing debate on whether palliative removal of the primary tumor may result in a survival benefit for patients with incurable stage IV pancreatic neuroendocrine tumors (P-NET). The objective of this study was to assess whether palliative resection of the primary tumor in patients with incurable stage IV P-NET has an impact on survival.
Gesehen am 03.06.2020